TINJAUAN TERHADAP TRANSAKSI KONTRAK PERPINDAHAN PEMAIN SEPAK BOLA CLUB SEMEN PADANG F.C - Naldi Gantika naga; Fahrul Yuwanda fahrul (Ekasakti Jurnal Penelitian dan Pengabdian, 2020)
Football fame is no longer just a game or a physical sport, but football has become a profitable business for some. No exception in Indonesia, the popularity and existence of the business in it have made the foot sport intensively held in villages, cities with the format of village tournaments or better known as Tarkam until an official competition under the PSSI was called Liga 1. A tantalizing profit for those who are involved in football is one of the bases for entrepreneurs or millionaires to establish young football academies, invest, and establish professional clubs.